Overcoming Barriers to Integrating Behavioral Health and Primary Care Services - Kyle L. Grazier; Mary L. Smiley; Kirsten S. Bondalapati (Journal of Primary Care & Community Health, 2016)
Objective: Despite barriers, organizations with varying characteristics have achieved full integration of primary care services with providers and services that identify, treat, and manage those with mental health and substance use disorders. What are the key factors and common themes in stories of this success? Methods: A systematic literature review and snowball sampling technique was used to identify organizations. Site visits and key informant interviews were conducted with 6 organizations that had over time integrated behavioral health and primary care services. Case studies of each organization were independently coded to identify traits common to multiple organizations. Results: Common characteristics include prioritized vulnerable populations, extensive community collaboration, team approaches that included the patient and family, diversified funding streams, and data-driven approaches and practices. Conclusions: While significant barriers to integrating behavioral health and primary care services exist, case studies of organizations that have successfully overcome these barriers share certain common factors.